Acme - Sinnickson, Robert, 1827-
Signed holograph poem entitled "Acme" written by Sinnickson to commemorate the marriage of Grover Cleveland and Frances Folsom Cleveland.
Poet, printer, and editor.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Cleveland, Frances Folsom, -- 1864-1947 -- Poetry; Cleveland, Grover, -- 1837-1908 -- Poetry; Marriage -- Poetry; Editors; Poets; Printers